2007
DOI: 10.1007/s10803-007-0430-0
|View full text |Cite
|
Sign up to set email alerts
|

Gross Motor Development, Movement Abnormalities, and Early Identification of Autism

Abstract: Gross motor development (supine, prone, rolling, sitting, crawling, walking) and movement abnormalities were examined in the home videos of infants later diagnosed with autism (regression and no regression subgroups), developmental delays (DD), or typical development. Group differences in maturity were found for walking, prone, and supine, with the DD and © Springer Scicnce+Business Media, LLC 2007 Correspondence to: Sally Ozonoff, sjo7.onoff@ucdavis.edu. HHS Public Access Author Manuscript Author Manuscript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
192
1
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(218 citation statements)
references
References 30 publications
15
192
1
10
Order By: Relevance
“…Several studies have reported on motor milestones, either through home-video analysis (Baranek, 1999;Gernsbacher, Sauer, Geye, Schweigert, & Hill Goldsmith, 2008;Ozonoff et al, 2008;Teitelbaum, Teitelbaum, Nye, Fryman, & Maurer, 1998) and/or interviewing parents (Gernsbacher et al, 2008;Kopp et al, 2010;Lloyd, MacDonald, & Lord, 2013;Ozonoff et al, 2008;Sumner et al, 2016). These studies are methodologically problematic in the respect that video rating is open to human error (though most studies blind raters to diagnosis), videos cover a small and selective snapshot of early life, and retrospective reports are open to inaccuracy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported on motor milestones, either through home-video analysis (Baranek, 1999;Gernsbacher, Sauer, Geye, Schweigert, & Hill Goldsmith, 2008;Ozonoff et al, 2008;Teitelbaum, Teitelbaum, Nye, Fryman, & Maurer, 1998) and/or interviewing parents (Gernsbacher et al, 2008;Kopp et al, 2010;Lloyd, MacDonald, & Lord, 2013;Ozonoff et al, 2008;Sumner et al, 2016). These studies are methodologically problematic in the respect that video rating is open to human error (though most studies blind raters to diagnosis), videos cover a small and selective snapshot of early life, and retrospective reports are open to inaccuracy.…”
mentioning
confidence: 99%
“…Nor did Lloyd et al's (2013) analysis of the few items concerning motor milestones in the ADI-R (Le Couteur, Lord, & Rutter, 2003). Gernbacher et al's (2008) parental reports suggest a delay in crawling and in numerous oral-motor milestones such as blowing kisses; Ozonoff et al's (2008) parental reports reflect significant delays in walking and trends towards delays in crawling and sitting. This study differentiated between autistic children with and without early regression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Autism was first noticed by Kanner in 1943, as cited in [2,3,5,6] and reported that they have poor motor and imitation tasks and this has been established by many researches [2,3,4]. Several researches have been done to explain the symptoms of autism.…”
Section: Introductionmentioning
confidence: 99%
“…However; it is difficult to detect autism in infants based on psychology test in motor movement [5,6], while researchers revealed that autistic individual between the ages of 9 to 10 have deficits in motor task [7]. Even though it may be possible to detect poor motor movement for autism, it is not usually adopted in most cases to diagnose autism; most clinics depend on social defects rather than other behavior which are not shown in the early age.…”
Section: Introductionmentioning
confidence: 99%